2021
DOI: 10.1038/s41598-021-93517-w
|View full text |Cite
|
Sign up to set email alerts
|

Tunable multichannel Photonic spin Hall effect in metal-dielectric-metal waveguide

Abstract: The discovery of Photonic spin Hall effect (PSHE) on surface plasmon polaritons (SPPs) is an important progress in photonics. In this paper, a method of realizing multi-channel PSHE in two-dimensional metal-air-metal waveguide is proposed. By modulating the phase difference $$\phi$$ ϕ and polar angle $$\theta$$ θ of the dipole source, the SPP can propagate along a specific channel. We further prove that PSHE results from the component wave i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Discussion. -According to the complete control theory, those already reported [16][17][18][19][20] about the scattering in 4-channel structures can be more deeply understood. Since the circular polarized incident light contains only two sources (two polarized components), it is not the complete set of sources for a 4-channel structure.…”
Section: Applications Of the Theory -2-channel Structuresmentioning
confidence: 94%
“…Discussion. -According to the complete control theory, those already reported [16][17][18][19][20] about the scattering in 4-channel structures can be more deeply understood. Since the circular polarized incident light contains only two sources (two polarized components), it is not the complete set of sources for a 4-channel structure.…”
Section: Applications Of the Theory -2-channel Structuresmentioning
confidence: 94%
“…In June 2012, Yang Jun, Chen Heming and others designed a 1×4 waveguide beam splitter which introduced Y-shaped waveguides into photonic crystal directional couplers and used the transmission characteristics of high-efficiency photonic crystal waveguides to achieve beam splitting. Most importantly, this structure can achieve high light transmittance for each output branch by adjusting the dielectric column radius in the photonic crystal [6] . In 2020, Jiang DanZong proposed a light-controlled beam splitter with adjustable Y-type terahertz wave splitter based on two-dimensional photonic crystals, which achieves a beam splitting ratio of a specific wavelength by changing the light intensity [7] .…”
Section: Research Statusmentioning
confidence: 99%
“…According to the spin coupling theory, the incident spin determines the spin of SPP, and then the spin of SPP determines the propagation direction of SPP. Recently, it has been found that the asymmetric scattering of PSHE is caused the component wave interference (CWI) of electric or magnetic dipoles 20 22 . According to CWI theory, the propagation direction of SPP is determined by the incident spin, and then the spin of SPP is determined by the spin orbit locking of SPP.…”
mentioning
confidence: 99%